Human Factors in Cyber Deception: Psychological Manipulation in Cognitive Honeypots (MSW Management Journal, 2026)
Cyber deception has emerged as a proactive defence strategy to mislead, delay, and deter attackers while collecting actionable intelligence. Among various deception mechanisms, cognitive honeypots stand out by exploiting psychological manipulation and behavioral tendencies of human adversaries. Unlike traditional honeypots that rely on technical traps, cognitive honeypots leverage human factors such as curiosity, overconfidence, risk perception, and decision-making biases to influence attacker behavior. This paper examines the interplay between human psychology and cyber deception, highlighting how cognitive honeypots exploit cognitive vulnerabilities to enhance cybersecurity. The study synthesizes insights from cognitive psychology, behavioral economics, and cybersecurity research to explain attacker profiling, manipulation techniques, and ethical implications. Furthermore, case studies illustrate real-world and experimental deployments of cognitive honeypots, underscoring their potential to strengthen adaptive defence. The paper concludes by discussing challenges such as attacker adaptability, ethical dilemmas, and the need for interdisciplinary frameworks that combine technology and psychology for effective cyber deception.